2005
DOI: 10.1158/0008-5472-can-04-3913
|View full text |Cite
|
Sign up to set email alerts
|

PIK3CA Mutations Correlate with Hormone Receptors, Node Metastasis, and ERBB2, and Are Mutually Exclusive with PTEN Loss in Human Breast Carcinoma

Abstract: Deregulation of the phosphatidylinositol 3-kinase (PI3K) pathway either through loss of PTEN or mutation of the catalytic subunit A of PI3K (PIK3CA) occurs frequently in human cancer. We identified PIK3CA mutations in 26% of 342 human breast tumor samples and cell lines at about equal frequency in tumor stages I to IV. To investigate the relationship between PTEN and PIK3CA, we generated a cohort of tumors that had lost PTEN expression and compared it with a matched control set that had retained PTEN. A highly… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

93
680
17
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 803 publications
(796 citation statements)
references
References 19 publications
(33 reference statements)
93
680
17
6
Order By: Relevance
“…This suggests that PTEN alterations are more commonly involved in a distinct pathway of CRC tumorigenesis that is separate from the pathway of mismatch repair deficiency. Because both PIK3CA mutations and loss of PTEN function are thought to activate PI3K/AKT pathway, it is speculated that PIK3CA mutations and loss of PTEN expression are mutually exclusive (Broderick et al, 2004;Frattini et al, 2005;Saal et al, 2005). However, we have found no association between PTEN alteration and PIK3CA mutations.…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…This suggests that PTEN alterations are more commonly involved in a distinct pathway of CRC tumorigenesis that is separate from the pathway of mismatch repair deficiency. Because both PIK3CA mutations and loss of PTEN function are thought to activate PI3K/AKT pathway, it is speculated that PIK3CA mutations and loss of PTEN expression are mutually exclusive (Broderick et al, 2004;Frattini et al, 2005;Saal et al, 2005). However, we have found no association between PTEN alteration and PIK3CA mutations.…”
Section: Discussioncontrasting
confidence: 74%
“…Sequencing of PIK3CA exons 9, 20 was done by PCR amplification and direct sequencing of both strands for all CRC cases and their matched normal samples as previously described (Saal et al, 2005;Abubaker et al, 2007). In brief, step-down PCR was performed as follows: after a 10-min denaturing at 95 1C, the PCR was run with each temperature for 1 min at five step-down steps, for two cycles each.…”
Section: Microsatellite Markers and Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have pointed out that PIK3CA mutations were mutually exclusive with the mutations of PTEN, suggesting that oncogenic signaling occur either through activation of PIK3CA or inactivation of PTEN. 9 However, recently published studies in endometrial carcinoma demonstrated that coexistent mutations of PIK3CA and PTEN genes are indeed possible. 10 Our case also showed that such combination can also occur in mammary ACC.…”
Section: Discussionmentioning
confidence: 99%
“…11 PIK3CA mutations have been detected in 8-40% of breast carcinomas and are associated with poor outcome. 12 Saal et al 9 identified PIK3CA mutations in 26% of 342 breast carcinoma specimens at about equal frequency irrespective of the tumor stage.…”
Section: Discussionmentioning
confidence: 99%